1999
DOI: 10.1253/jcj.63.929
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between QT Dispersion and Ventricular Arrhythmias In Uncomplicated Isolated Mitral Valve Prolapse

Abstract: itral valve prolapse (MVP) is the most commonly diagnosed valvular heart disease, especially in the young, and affects 5% of the community. 1 Although it is reported that MVP has a good prognosis and a low incidence of complications, 2 it is obvious that even a rare complication will affect many individuals due to the high incidence of MVP in the general population. 3 However, some reports point out that these complications are not as rare as was thought, 4,5 the main entities being endocarditis, cerebrovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…We found that QT dispersion and QTc increased as the degree of ventricular arrhythymias increased and QT dispersion was significantly higher in the group who had more than 10 VPBs in 24 hours and/or who had complex ventricular arrhythymias compared to healthy children who had no VPBs. Different results have been reported in studies related with QT interval in adults with primary MVP (7,8). Kulan et al (7) found no significant difference between adult patients with MVP and healty controls in terms of QTc.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…We found that QT dispersion and QTc increased as the degree of ventricular arrhythymias increased and QT dispersion was significantly higher in the group who had more than 10 VPBs in 24 hours and/or who had complex ventricular arrhythymias compared to healthy children who had no VPBs. Different results have been reported in studies related with QT interval in adults with primary MVP (7,8). Kulan et al (7) found no significant difference between adult patients with MVP and healty controls in terms of QTc.…”
Section: Discussionmentioning
confidence: 88%
“…In studies involving adults, a close relation between ventricular arrhythymias and QT dispersion which is a criterion for regional differences in the ventricular repolarization period has been reported (7)(8)(9). In the study of Kulan et al (7) which involved 64 adult patients with primary MVP and 80 healthy individuals, it was shown that QT dispersion increased in the patient group and there was a correlation between the increase in QT dispersion and complex ventricular arrhythymias.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations